Fabrication and characterization of YSZ/ScSZ bilayer electrolyte via Cold- Isostatic Pressing (CIP) method for intermediate temperature-solid oxide fuel cell (IT-SOFC) application - Mat Z.A.; Nadaraja S.K.; Zakaria Z.; Hassan S.H.A.; Kar Y.B.; Tan C.Y.; Somalu M.R. (Penerbit UTHM, 2023)
Solid oxide fuel cell (SOFC) technology has advanced significantly in the recent years, and now is an interest of many renewable energy-related industries to invest. However, the main issue of SOFC is the high operating temperature that negatively influence its performance. To reduce the temperature, a method of using bilayer electrolyte is proposed. In this study, a bilayer electrolyte of Yttria-Stabilised Zirconia (YSZ) and Scandia-Stabilized Zirconia (ScSZ) is used with the objective to reduce the temperature of SOFC to intermediate temperature ranges. To achieve the objective, bilayer YSZ/ScSZ electrolyte has been fabricated at different compositions using cold-pressing method. The pellets were sintered at three different temperature of 1350 C, 1450 C and 1550 C. In this studies, all the prepared pellets were characterized under Scanning Electron Microscopy (SEM) to examine its microstructure, Archimedes Method to measure the density and Electochemical Impedance Spectroscopy (EIS) to measure the conductivity. The results show that all of produced pellets are dense and ionic conductivity showed a rising trend as sintering temperature increases. Based on this study, the best composition is the pellet with combination of 25% YSZ: 75% ScSZ sintered at 1450 C. Universiti Tun Hussein Onn Malaysia Publisher's Office.